2023
DOI: 10.3390/app13148318
|View full text |Cite
|
Sign up to set email alerts
|

Role of White Rot Fungi in Industrial Wastewater Treatment: A Review

Abstract: White Rot Fungi (WRF) are a class of microorganisms widely understood for their ability to breakdown an extensive range of pollutants generally found in industrial wastewater. This specific literature review centers on the abilities of the White Rot Fungi to treat industrial wastewater, analysis of the biodegradation mechanism, future applications, and scaling up for practical implementation. WRF usually carry out the degradation process with ligninolytic enzyme by targeting complex industrial pollutants, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 121 publications
0
11
0
Order By: Relevance
“…Their significant production of extracellular enzymes such as peroxidases, laccases, and phenol oxidases enables the effective reduction of phenolic compounds into simpler, less ecotoxic molecules [23][24][25]. Studies have underscored the remarkable potential of white-and brown-rot fungi in phenol reduction, achieving the removal of up to 100% of phenolic forms in industrial effluents [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Their significant production of extracellular enzymes such as peroxidases, laccases, and phenol oxidases enables the effective reduction of phenolic compounds into simpler, less ecotoxic molecules [23][24][25]. Studies have underscored the remarkable potential of white-and brown-rot fungi in phenol reduction, achieving the removal of up to 100% of phenolic forms in industrial effluents [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the sorption of pollutants into activated carbon, carbon nanotubes and fullerene have been used for the treatment of polluted wastewater [ 14 ]. Even though it has been demonstrated that these techniques are efficient, they have disadvantages, such as the generation of harmful byproducts, the accumulation of high volumes of residuals and high costs [ 15 , 16 , 17 ], consequently restraining their application in environmental remediation [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, white rot fungi (WRF), as organisms living on wood, have evolved to degrade major wood polymers, including lignin. Due to the broad substrate range of their ligninolytic enzymes, WRF are exceptional microorganisms that show extraordinary capacities to degrade a widespread range of lignin-related compounds such as xenobiotics, including synthetic dyes, polychlorinated biphenyls, organophosphate pesticides and polycyclic aromatic hydrocarbons [ 5 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Water treatment using fungal technology, also called mycoremediation, is an alternative treatment to water treatment using biological processes, specifically bacterial, due to limitations in removing all pollutants simultaneously [ 13 ]. Mycoremediation offers extensive removal of pollutants, such as heavy metals [ 14 ], antibiotics [ 15 ], dyes [ 16 ], aromatic hydrocarbons [ 17 ], organic materials, and non-organic pollutants [ 18 ], due to varying mechanistic properties.…”
Section: Introductionmentioning
confidence: 99%